VisUAM: A web-based tool for data visualization in scientific research - Pérez-Espinosa, Adriana; Aguilar-Cornejo, Manuel; Dagdug, Leonardo; Quiroz-Fabián, José Luis; Román-Alonso, Graciela; Castro-García, Miguel A. (SoftwareX, 2024)
Visualization is essential for interpreting data, especially in scientific research where datasets often come from experiments or simulations. Data visualization techniques vary based on the data type. For example, mapping can illustrate city traffic incidents, while bar plots can identify the most common incidents. This paper presents VisUAM (Visualizador UAM), a web-based tool for creating graphics from various datasets across any domain. The current version of VisUAM supports data from three scientific software tools: Pore Networks, Voronoi Diagrams, and Particle Diffusive Simulator. VisUAM’s architecture allows easy integration of any data type and supports multi-dimensional visualizations, including 2D, 3D, and animations. Its flexibility, web-based accessibility, and adaptability to new visualization needs make VisUAM a versatile and comprehensive platform for researchers.